2005
DOI: 10.1111/j.0269-283x.2005.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Musca domestica is not a vector of Thelazia callipaeda in experimental or natural conditions

Abstract: Thelazia callipaeda Railliet and Henry (Spirurida: Thelaziidae), commonly called oriental eyeworm for its widespread presence in the Far East, has been recently found to affect dogs, cats and foxes in northern and southern Italy. Although the biology of T. callipaeda in the definitive hosts has been recently investigated, many doubts still remain about its biology in insect vectors. It has been suggested that more than one species of Diptera, namely Musca domestica Linnaeus (Diptera: Muscidae) and Amiota okada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Larvae were reared and all pupae allowed to develop until the emergence of the imagos, according to the procedures described in Otranto et al (2005). Flies that emerged from each collection were divided into four groups, which were killed as described above on post‐emergence days 0, 1, 2 and 3, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Larvae were reared and all pupae allowed to develop until the emergence of the imagos, according to the procedures described in Otranto et al (2005). Flies that emerged from each collection were divided into four groups, which were killed as described above on post‐emergence days 0, 1, 2 and 3, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Specimens were quenched in liquid nitrogen and genomic DNA was extracted (Otranto et al , 2003, 2005) from each pool of flies using a commercial kit (DNeasy Tissue Kit; Qiagen GmbH, Hilden, Germany) and stored at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that more than one species of Diptera, namely Musca domestica Linnaeus (Diptera: Muscidae) and Amiot okadai Maca (Diptera: Drosophilidae), may be involved in the transmission of T. callipaeda; however, so far, this was not proved in research conducted in experimental and natural conditions (12). …”
Section: O R P H O L O G I C a L C H A R A C T E R I S T I C S A N mentioning
confidence: 99%
“…In France, ocular infections of carnivorous T. callipaeda have been reported (9). This infection is also common in dogs and cats in Italy (12)(13)(14). Several studies have shown that the disease is endemic throughout Italy (13,14).…”
Section: O R P H O L O G I C a L C H A R A C T E R I S T I C S A N mentioning
confidence: 99%
See 1 more Smart Citation